2006
DOI: 10.1071/wf05076
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of prescribed burning strategies in south-west Tasmania, Australia: effects on unplanned fires, fire regimes, and ecological management values

Abstract: Computer simulation modelling provides a useful approach for determining the trade-offs between the extent of prescribed burning and the long-term impacts of unplanned fires on management values. In the present study, FIRESCAPE-SWTAS, a process-based fire regime and vegetation dynamics model, was used in the World Heritage Area of south-west Tasmania, Australia, to investigate the implications of different prescribed burning treatments on identified management objectives. Treatments included annual prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…Therefore, to have a substantial effect on unplanned fire area, a very considerable proportion of the landscape would need to be treated. This conclusion has been reached by several previous modelling studies based on well-established fire spread equations, both in Australia (Bradstock et al 1998a(Bradstock et al , 1998bKing et al 2006King et al , 2008 and elsewhere (Pinol et al 2005;Cary et al 2009). …”
Section: <0001supporting
confidence: 49%
“…Therefore, to have a substantial effect on unplanned fire area, a very considerable proportion of the landscape would need to be treated. This conclusion has been reached by several previous modelling studies based on well-established fire spread equations, both in Australia (Bradstock et al 1998a(Bradstock et al , 1998bKing et al 2006King et al , 2008 and elsewhere (Pinol et al 2005;Cary et al 2009). …”
Section: <0001supporting
confidence: 49%
“…The results of simulation studies often reach the opposite conclusion to those empirical studies: that small amounts of treatment result in large reductions in area burnt by unplanned fires (Finney 2007;King et al 2006;Loehle 2004). Loehle (2004) coined the term leverage to mean the area of unplanned fire reduction (from an untreated state) obtained per unit of treatment.…”
Section: Introductionmentioning
confidence: 66%
“…Finney (2007) found that treating 1% of the landscape per annum in an optimised design reduced the probability of burning by about 60%. King et al (2006) found that treating 5% of the landscape reduced the area burnt by about 50%. Given these disparities, there is a need for synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the strategic spatial arrangement of the EDS areas has enhanced the return for effort above parity. Such an effect has been demonstrated in simulation studies (Finney 2001;King, Cary et al 2006). However, there are other potential causes for the large reduction in LDS, including a reduction in LDS ignitions due to improved community awareness brought about by the WALFA program.…”
Section: Discussionmentioning
confidence: 96%
“…This result is similar to that found by (Price and Bradstock 2011) for the forests of the Sydney region in eastern Australia, where there was no evidence of nonlinearity and an empirical study in Jarrah forests of Western Australia (Boer, Sadler et al 2009), which found a weak concave relationship. However, there was a marked concave relationship in a simulation study of Tasmanian forests (King, Cary et al 2006). A linear relationship implies that there will be a certain level of treatment at which wildfires are eliminated.…”
Section: Discussionmentioning
confidence: 99%